TEACHING WRITING RECOUNT TEXT AT EIGHT GRADE USING THINK-TALK-WRITE TECHNIQUE BY DIGITAL STORYTELLING - Baidhowi, Muhammad Faozi; Pamungkas, Mundriyah (PROJECT (Professional Journal of English Education), 2020)
Based on the fact that the students writing ability, was very low, so the students had difficulties in writing especially writing recount text. The aims of this research to find out: 1) The implementation of the scenario in teaching English writing recount text using think-talk-write technique by digital storytelling 2) The students difficulties in learning writing recount text using think-talk-write technique by digital storytelling. This study used descriptive qualitative research. The subject of the study was the eight grade students in one of junior high school that consist of twenty students. The instrument used in this study were observation sheet and questionnaire. The results of this study indicated that the implementation of teaching and learning process was done in accordance with the scenario that had been made by the researcher. The initial assignment was given to the students to know what are the difficulties faced by the students. Based on the result, it could be mentioned that the students difficulties were the use of grammar, poor vocabulary-especially in spelling and how to use appropriate vocabulary. After learning using the TTW technique, the students could overcome their difficulties. They could understand better the use of grammar and structure, appropriate vocabulary and better in spelling. Keywords:  Think-Talk-Write, Digital Storytelling, Writing